Customs Risk Management in Albania. An important Step towards Integration in the European Union - Bardhi, Ejona (European Journal of Sustainable Development, 2015)
The customs are involved within the state administration; they are responsible in collecting the customs liabilities as well as for the international flux of goods. This responsibility is provided in the national legislation and in the international rules of trade. The customs are a unique body, among all the state bodies due to the fact that they have the position of both national and international agency. They are positioned at the international borders not only as an expression of the sovranity of a country but as well as national guard against all the external threats against health, security, environment and domestic industry. Te importance of the customs is increasing due to the increase of international trade as well as of the increasing request on security. The customs administration is reviewing all the operations towards the international standards and best practices to realize a suitable customs administration which would lead in easing the international trade. The importance of customs procedural requests is increasing as a consequence of the increase of the international trade during the latest years. The increase of customs procedural requests increased adding the costs of government, business and consummators. The customs are responsible for achieving the competitive objectives, as well as for controlling the borders and offering facilitations in international legal trade. The facilitation of the trade through the diminution of customs payments, is important in economies in development and in the developed ones, due to the contribute in exports growth, in improving the concurrence of goods and services at the global market, in attracting more IHD-s, in increasing the participation of small and medium enterprises at the international market. The customs are responsible for the facilitation of trade, for this reason they are in continuous process of reformation and modernization in the under development and developed countries. Due the rules based at the trade policies of WTO, it was made possible that the fees were decreased and non-fee barriers are in cancelations. The customs administration is excepted to bring incomes, to stop the import of not safe or banned goods and to the fight the narcotics trade. It is excepted to fulfill these targets effectively without hamper the commercial facilitations. This paper has as the main objective to treat the management of risk at the customs. During this paper I will treat the main problematic of the customs administrations in Europe and Albania, including theory and practice aspects. This paper treats: controls after the passing permission at the Customs, levels of risk management, costs and benefits of the techniques of risk management, management of facilitation and customs activity, the importance of information of customs system, important problematic in customs activity, rule of origin and its importance and finally the transit as the main mean of trade facilitation. Keywords: Management, risk, customs, administration, trade